Nutritional intake of French soccer players at the Clairefontaine training center - Leblanc, C.; Le Gall, F.; Grandjean, V.; Verger, P. (International Journal of Sport Nutrition and Exercise Metabolism, 2002)
Young, French male athletes undergoing intensive elite sports training at the National Training Centre in Clairefontaine served as the subjects (N = 180; age range: 13 to 16 years) in a 3-year dietary survey aimed at characterizing their nutritional intake in terms of energy, macronutrients, calcium, and iron. Each year, the subjects were grouped by level into 3 promotions so that 9 groups could be studied. Dietary intake data were collected each year for each subject in the 9 groups, using a 5-day food record. The results showed that their total energy intake (TEI) was insufficient for athletes (ranging from 2352 ± 454 to 3395 ± 396 kcal/d as opposed to the recommended range of between 3819 and 5185 kcal/d). Furthermore, their diet was unbalanced, with too great an emphasis upon fatty foods (29.1 ± 2.8 to 34.1 ± 3.1% TEI vs. the 20% recommended), to the detriment of carbohydrates (48.5 ± 4.3 to 56.6 ± 3.1% TEI vs. the 55 to 60% recommended). The calcium intake was too low in 5 of the 9 groups while, in contrast, the iron intake was satisfactory in all groups. Furthermore, during this 3-year period at the Clairefontaine Centre, the subjects significantly (p < .05) improved their calcium and iron intakes (1021 ± 197 and 12 ± 2 mg/d in 1996, 1299 ± 155 and 16 ± 2 mg/d in 1997, and 1252 ± 184 and 17 ± 2 mg/d in 1998). This rise in micronutrient intakes may have been due to a physiological adaptation to growth or to the positive effects of courses on nutrition given during their stay at the Centre.